Investigating the Efforts Being Made to Promote the Healthy Aging of the Elderly in Lugazi Central Division. - Yahaya Wandega (Uganda Christian University, 2024)
This study investigates the efforts being made in promoting the healthy aging of the elderly in Kikawula Lugazi Central Division, Buikwe District. On the older people aged 60 years and above including the demographic characteristics and healthcare of the elderly. A survey of 30 respondents revealed a predominantly male population (67%) significant age range distribution 60_64(23%), 65_69 (17%), 70_74 (20%). Marital status , education and occupational varied with (50%) married, (33%) primary education and (50%) farmers. Religious affiliations included Catholicism (50%), Anglicanism (17%) and Islam (33%).the findings highlighted the need for targeted interventions such as men’s health workshops, retirement planning , spousal relationships support, specialised education, occupational related health considerations and culturally sensitive healthcare .this study informs strategies for promoting healthcare, social support and community-driven interventions to the elderly population’s unique needs. The study used a mixed method of data collection tools and examined healthcare, social support and community-driven interventions for the elderly in kikawula Lugazi Central Division. Local nongovernmental organisations, community healthcare canters and private clinics were identified as the key players. However, (73.33%) of the respondents were unaware of the service. The study highlighted key stakeholders provided comprehensive healthcare services, including doctors consultations , occupational therapy and community gatherings. Findings emphasized the need to improve for addressing financial logistical constraints to improve health care access and enhance overall well-being.